Real-Time Monitoring System for Workers' Behaviour Analysis on a Large-Dam Construction Site. (7th October 2013) - Lin, Peng; Li, Qingbin; Fan, Qixiang; Gao, Xiangyou
Abstract : This paper studies the feasibility of a real-time monitoring system to provide prompt analysis support of workers' behaviour on dam construction sites. The system makes use of wireless sensor tracking technology and a set of servers for the running of software, handling collected data, real-time site state visualization, and remote interaction communications. The low-level ZigBee-based tracking technology network hardware utilizing fingerprinting software technology was employed. The system was found to be able to cover a large field whilst retaining its simple and easily deployable features. The proposed system was successfully implemented on the Xiluodu arch dam construction site and ultimately helped overcome the original shortcomings in worker safety management and has advanced the means of administration and management's awareness and culture to new levels. The field tests also show that the received signal strength indicator (RSSI)-based localization algorithm implemented on ZigBee devices is reliable and is accurate enough at 3 to 5 meters. In conclusion, the system proved to be very useful for the management of field safety worker behaviour analyses in the case of such a high arch dam and also for similar hydraulic projects.